Pengaruh Self-Compassion Dan Dukungan Sosial Terhadap Work-Family Conflict Pada Wanita Di Kota Makassar - Rahmat, Abdul; Asri, Asmulyani; Wulandari, Ririn Mamiek (Universitas Negeri Makassar, 2021)
The purpose of this study was to determine how the effect of self-compassion and social support on work-family conflict among women in Makassar City. This study uses a correlational method that uses a quantitative approach by providing a scale. The population in this study are women who live in the city of Makassar. Characteristics include those who work, at least three years of marriage, and have children. The data collection technique in this study is a scale distribution in the form of a Likert scale. The results of measurements on the subject will be analyzed using data analysis methods, namely simple linear regression analysis and followed by categorization using SPSS.